Design and Build of a Multi-Zone Beamforming Speaker - Khemapat Tontiwattanakul; Jiraphat Sueprasert; Dech Nawik; Pitak Thumwarin; Nachanant Chitanont (My University, 2025)
Recently, beamforming speaker for multi-zone sound production is an application that is of interest such as conference system, public address, home cinema, and gaming. This paper presents a design of a speaker array and DS beamforming aiming to use for product advertising such that the speaker can be installed on the shelf. The limit of the space and the usable frequency range are the challenges of this work. The design of the speaker cabinet and the beamforming algorithm will be discussed.
Keywords: Speech and Audio Processing